Nitrate-nitrogen sufficiency ranges in leaf petiole sap of pac choi grown with organic and conventional fertilizers - Elfar Altamimi, May (Kansas State University, 2010)
Petiole sap nitrate-nitrogen (NO3-N) analysis with handheld meters is a valuable tool in applying in-season nitrogen (N) for many crops. Sufficiency levels have been determined for several leafy green crops, including lettuce (Lactuca sativa L.) and cabbage (Brassica oleracea L.), but not for pac choi (Brassica rapa L.). The response of pac choi to different fertilizer rates and sources [conventional and organic] has established optimal soluble N application rates and Cardy meter sufficiency ranges. Greenhouse experiments were conducted during summer and fall of 2008 in Manhattan, KS. Conventional soluble fertilizer was formulated from inorganic salts with a 4 NO3-N: 1 ammonium ratio. Phosphorus was held at 1.72mM and K at 0.83mM for all treatment levels. The organic soluble fertilizer, fish hydrolyzate (2N:1.72P:0.83K), was diluted to provide the same N levels as with conventional treatments. Both fertilizers were applied at rates of 0, 32, 75, 150, 225, 300, and 450 mg. L-1. Seedlings were transplanted and fertilizer application began at 18 days. Plants were harvested at seven weeks (five weeks post transplanting) after receiving 15 fertilizer applications during production. Samples of the most recently matured leaves were harvested weekly and analyzed for petiole sap NO3-N and leaf blade total N concentration. Leaf count, leaf length, and chlorophyll content were also measured weekly. Fresh and dry weights were determined on whole shoots and roots. Optimum yield was achieved at the 150 mg. L-1 fertility rate with both conventional and organic fertilizers. Field and high tunnel experiments were conducted during fall 2008 to validate the sufficiency ranges obtained from the greenhouse studies. Based on field and high tunnel results, sufficiency levels of NO3-N for pac choi petiole sap during weeks 2 to 3 of production were 800-1500 mg. L-1, and then dropped to 600-1000 mg. L-1 during weeks 4 through harvest for both conventional and organic fertilizers sources. These ranges could vary based on the variety of the crop, the fertility of soil, and certain environmental factors such as photoperiod, light intensity. However, we found that petiole sap nitrate always increased to the point associated with the maximum biomass, followed by a plateau where sap nitrate remained constant. This characteristic of the Cardy meter can provide the growers with a practical methodology to generate their standard curves under specific conditions to guide in-season N applications. Total N in leaf tissue showed fewer fertilizer rate effects than petiole sap NO3-N. Chlorophyll content was not useful in evaluating pac choi N status.
Keywords: Pac choi; Nitrate nitrogen; Sufficiency ranges; Organic fertilizers; Conventional fertilizers; Brassica rapa; Agriculture, General (0473); Agriculture, Soil Science (0481)